Freezing Combined with Electrical and Magnetic Disturbances - Xanthakis, Epameinondas; LeBail, Alain; Havet, Michel (My University, 2014)
In this chapter, novel freezing methods involving the application of electrical and magnetic disturbances are covered. Freezing is one of the most popular and widely used food preservation methods. The freezing process of food matrices is based on their dominant constituent, which is water. The phase transition of liquid water into ice during the crystallization stage is closely related to the final quality of the frozen product. For this reason, several emerging technologies have been developed to control the crystallization process and to improve the formation as well as the growth of ice crystals. This chapter contains an overview of the theoretical and experimental methods available for the application of static electric, oscillating electric, and magnetic fields related to the freezing process. Understanding the importance of these techniques for improving freezing processes requires analyzing the mechanisms that arise from the findings of these studies.
Keywords: Electric field; Food; Freezing; Magnetic field; Oscillating field; Patents; Water